Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

Tributyltin exposure induces histopathological and ultrastructural adrenal damage and increases the HMGB1/Beclin-1/NF-κB signals in rats: The role of recovery - Samar Mortada Mahmoud; Heba Osama Mohammed; Marwa A. El-Beltagy; Heba H. Mahboub; Amira Hamed Mohamed soliman (Tissue and Cell, 2026)

Alleviating role of taurine against tartrazine-induced hepatotoxicity in albino rat: Biochemical, histopathological, immunohistochemical, and gene expression assessments - Samar Mortada Mahmoud; Reham H. Abdel-Kareem; Sara F. Saadawy; Heba H. Mahboub; Abdelfattah M. Abdelfattah; Amira Hamed Mohamed Soliman (Tissue and Cell, 2026)

Effects of dietary chitosan–flaxseed oil nanoemulsion on growth, economic performance, immunity, intestinal health, and cold-stress resistance in Nile tilapia (Oreochromis niloticus) - Randa Y. Thabet; Shaimaa A. A. Ahmed; Emad Sakr; Heba H. Mahboub; Hebatallah Abdel Moniem; Mohamed Y. M. Aly; Fatma Mahsoub; Sara E. Shahin; Khaled Yehia Farroh; Yasmine A. Mansour; Mahmoud I. M. Darwish; Abdallah Tageldein Mansour; et al. (Veterinary Research Communications, 2026)

Barbados aloe as a water-administered therapeutic against Pseudomonas aeruginosa infection in Clarias gariepinus: Effects on hemato-biochemical profiles, electrolyte homeostasis, antioxidant capacity, and tissue histology - Afaf N. Abdel Rahman; Heba H. Mahboub; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Mohamed Ashour; Roshmon Thomas Mathew; Mahmoud I.M. Darwish; Ahmed Abdou Elnegiry; Yasmin A. Reyad (Veterinary Research Communications, 2026)

Effects of dietary supplementation with chitosan nanogel on biochemical, antioxidant traits, and resistance to Aeromonas sobria infection, in Cyprinus carpio fingerlings - Hanan M. Alharbi; Heba H. Mahboub; Yasmine A. Mansour; Rasha M. M. Ezz-Eldin; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Tarek Khamis; Shaimaa A. A. Ahmed (Veterinary Research Communications, 2026)

Immune-antioxidant potential, splenic cytokines regulation, and tissue architecture restoration by grape seed oil nanoemulsion in Nile tilapia subjected to acrylamide toxicity - Shaimaa A. A. Ahmed; Heba H. Mahboub; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Hesham A. Hassanien; Ahmed Abbas; Saif M. Moafa; Haytham H. Abdelwahid; Khaled Yehia Farroh; Aaser M. Abdelazim; Yasmine A. Mansour; Randa Y. Thabet (Fish Physiology and Biochemistry, 2026)

Pumpkin seed oil improves hepatotoxicity in rats through inhibition of CYP2E1 and activation of Nrf2 signaling pathways - Noran W. Esmail; Sawsan M. El-sheikh; Reda M.S. Korany; Arwa A. Hassan; Sara M. Baraka; Hanan M. Alharbi; Ayman K. Ismail; Doaa A. Mansour; Heba H. Mahboub; Esraa.M. Fahmy (Tissue and Cell, 2026)

The effect of glyphosate-based herbicide on the postnatal development of the rat cerebellar cortex in male albino rats: Biochemical, anatomical, histopathological, and immunohistochemical assessments - Amira Hamed Mohamed Soliman; Hanan M. Alharbi; Mujtaba Farooq Rana; Heba H. Mahboub; Mohamed Wagdy; Rasha M.M. Ezz-Eldin (Tissue and Cell, 2026)

Ultrasonic irradiation for ZnO NPs Synthesis and their hepatoprotective effect against acetaminophen induced hepatic toxicity in albino rats: Biochemical, physiological, and histopathological assessments - Yasmine A. Mansour; Fady Sayed Youssef; Shaymaa Hussein; Hanan F. AbdEl_Halim; Sameh H. Ismail; Gehad G. Mohamed; Abdelfattah M. Abdelfattah; Rasha M.M. Ezz-Eldin; Heba H. Mahboub; Sherin Ibrahim (Tissue and Cell, 2026)

Heat stress remediation by dietary selenium nanoparticle supplementation in Nile tilapia, Oreochromis niloticus, reared in brackish water - Morteza Yousefi; Hossein Adineh; Zahra Koohestani; Zohreh Fazelan; Sanjay Kumar Gupta; Heba H. Mahboub; Seyyed Morteza Hoseini (Aquaculture, 2026)

Potential use of titanium nano-gel to palliate redox status, DNA damage, histopathological changes, and renal-hepatic disorders induced by Candida albicans in Clarias gariepinus - Randa Y. Thabet; Abdallah Tageldein Mansour; Heba H. Mahboub; Yousef Alkhamis; Hesham A. Hassanien; Ahmed Abbas; Adnan Alhaje; Sameh H. Ismail; Afaf N. Abdel Rahman; Heba Allah M. Elbaghdady (Veterinary Research Communications, 2025)

Benefits of fenugreek extract on renal tissue of ovariectomized rats treated with gentamicin: Biochemical, gene expression, and histopathological assessments - Sawsan M.A. El-Sheikh; Mohamed Gomaa; Randa Saied; Mohamed M.M. Metwally; Heba H. Mahboub; Hanan M. Alharbi; Aaser M. Abdelazim; Hanim S. Heikal; Tarek Khamis; Azza Galal (Tissue and Cell, 2025)

Dietary deacetylated chitin nanoparticles confer protection against diazinon toxicity in male African catfish: evaluation of immune-biochemical, antioxidant, and reproductive profiles - Hiam Elabd; Heba H. Mahboub; Heba S. Hamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samar Kamel; Amany Ramah; Sahar H. Orabi; Sherif M. Shawky; Simon J. Davies; Zeinab Hassan (Fish Physiology and Biochemistry, 2025)

Physiological, biochemical, apoptosis-linked gene expression, and histopathological insights in Nile catfish subjected to toxicity by magnetite nanogel - Yasmina K. Mahmoud; Shaimaa A. A. Ahmed; Heba H. Mahboub; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Ahmed A. Elnegiry; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Simon J. Davies; Mahmoud I. M. Darwish (Fish Physiology and Biochemistry, 2025)

The role of artichoke (Cynara scolymus) extract in Nile tilapia (Oreochromis niloticus) growth, and digestive enzymes, effect on oxidative and immune- and antioxidant-related gene expression before and after heat stress - Poulin Shohreh; Sedigheh Mohammadzadeh; Heba H. Mahboub; Pouya Ebrahimi; Hakimeh Gavzan; Mehdi Ahmadifar; Mohsen Shahriari Moghadam; Ehab EI-Haroun; Seyed Hossein Hoseinifar; Inês Guerreiro; Marina Paolucci; Ehsan Ahmadifar (Aquaculture International, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Expression profiling of antimicrobial peptides and immune-related genes in Nile tilapia following Pseudomonas putida infection and nano-titanium dioxide gel exposure - Heba H. Mahboub; Morteza Yousefi; Hosny Ahmed Abdelgawad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Emad Sakr; Tarek Khamis; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2025)

Effects of tea tree oil and cefepime treatments on morphological, genetic, histopathological, immunohistochemistry, and biochemical assessments in liver and kidney of Escherichia coli infected rats - Abdallah Tageldein Mansour; Amer Al Ali; Taghreed N. Almanaa; Dalia E. Altohamy; Rasha M.M. Ezz-Eldin; Mohammed S. Sobh; Aaser M. Abdelazim; Hanim S. Heikal; Heba H. Mahboub; Mohamed Aref (Tissue and Cell, 2024)

Dual effects of dietary Lactobacillus helveticus and chlorogenic acid on growth performance, digestibility, immune-antioxidant capacity and resistance against heat stress of juvenile common carp - Fatemeh Bakhtiari; Ehsan Ahmadifar; Mohsen Shahriari Moghadam; Sedigheh Mohammadzadeh; Heba H. Mahboub (Aquaculture International, 2024)

The influence of various doses of Moringa oleifera extract on the antioxidant trait, cytokines, reproductive hormones performance, and gonadal histological profiles of Nile tilapia - Fatma Abdel-monem Gad; Mahamoud Abdelghaffar Emam; Ramy M. Shourbela; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Heba H. Mahboub; Hiam Elabd (Aquaculture International, 2024)

In-water Bacillus species probiotic improved water quality, growth, hemato-biochemical profile, immune regulatory genes and resistance of Nile tilapia to Aspergillus flavus infection - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Heba A. Dowidar; Samia Elbahnaswy; Omaima H. Ezzo; Mohammad Bodrul Munir; Ahmed Jalal Khan Chowdhury; Nadia A. Abd Elghany; Heba H. Mahboub; Moaheda E. H. Eissa; et al. (Aquaculture International, 2024)

Toxicological insight of magnetite nanogel: neuro-ethological, hepato-renal, antioxidant, and histopathological traits in Clarias gariepinus - Samar Kamel; Shaimaa A. A. Ahmed; Asmaa Elsayyad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohamed Shaalan; Mohamed M. S. Gaballa; Heba H. Mahboub; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Zeinab Hassan (Aquaculture International, 2024)
Assessment of acute toxicity of magnetic nanogel (MNG) is crucial to conclude the safe applicable dose and to warrant its application in aquaculture. Therefore, the current study is a novel step to assess behavior, neuro-stress response, hepato-renal, oxidative, and histopathological variations produced by MNG’ acute toxicity in Clarias gariepinus . Two experiments were conducted: the first was a determination of the 96-h lethal concentration 50 (LC 50 ) of MNG in C. gariepinus . Meanwhile, the second was an assessment of the toxicological impacts of three different concentrations of MNG in C. gariepinus following a 10-day exposure period and a subsequent 10-day depuration trial. One hundred and eighty fish were allotted to four groups exposed to 0, 1/10, 1/8, or 1/5 96-h LC 50 of MNG. The outcomes exhibited that 96-h LC 50 of MNG for C. gariepinus was 44 mg/L. The subjected group to MNG induced a concentration-dependent elevation in the serum values of cortisol, alanine transaminase, aspartate transaminase, urea, and creatinine following MNG exposure. Marked elevation in the oxidative stress indicators (catalase (CAT), glutathione S-transferase activity (GST), and superoxide dismutase (SOD)) was also evident. Meanwhile, the value of the neurological biomarker, acetylcholinesterase (AChE), was markedly reduced in a concentration-dependent way. These biochemical changes were complemented by pathological alterations in the hepato-renal architecture. Interestingly, in response to the 10-day depuration period, most of the tested parameters were eliminated in C. gariepinus exposed to 1/10 of LC 50 . Conclusively, MNG can induce numerous adverse effects only at higher doses (1/5 and 1/8 of LC 50 ). Meanwhile, the lowest tested concentration of MNG (1/10 of LC 50 ) was safe for application in aquaculture practices with only mild disruptions in the bio-indices. In addition, a retrieval period of 10 days was sufficient to renovate these alterations only in fish exposed to the same concentration.

Influence of a mixture of oligosaccharides and β-glucan on growth performance, feed efficacy, body composition, biochemical indices, combating Streptococcus iniae infection, and gene expression of Nile tilapia (Oreochromis niloticus) - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Mohammad Bodrul Munir; Hoda A. Eissa; Sara F. Ghanem; Heba H. Mahboub; Nadia A. Abd Elghany; Hagar Sedeek Dighiesh; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2024)

The ameliorative role of magnetite nano gel against lead toxicity in Clarias gariepinus: growth, oxidant/antioxidant stress, gene expression, and histopathological alterations of gills - Abdallah Tageldein Mansour; Heba H. Mahboub; Tarek Khamis; Gehad E. Elshopakey; Morteza Yousefi; Khairiah Mubarak Alwutayd; Sameh H. Ismail; Afaf N. Abdel Rahman (Aquaculture International, 2024)

The protective efficacy of dual dietary rosemary plus cinnamon mix against lead nitrate-induced immune suppression, genotoxicity, and oxidant/antioxidant status in Nile tilapia fingerlings - Mohsen Abdel-Tawwab; Hiam Elabd; Heba H. Mahboub; Mohamed Ezzat M. Assayed; Heba S. Hamed; Asmaa Elsayyad; Engy M. M. Mohamed (Aquaculture International, 2024)
Lead (Pb) is a common heavy metal, which negatively influences the health and performance of aquatic organisms. The aquatic pollution with Pb is increasing day after day due to the increase in human activities, agricultural, and mining activities among others. Lead was regarded as oxidative stressor causing mutagenic and physiological disorders in aquatic animals. Hence, the current perspective assessed the promoting effects of dietary mixture of rosemary plus cinnamon (R + C) intervention on growth, hemato-biochemical, and hepatic oxidative biomarkers in Nile tilapia ( Oreochromis niloticus ) exposed to a sub-lethal dose of lead nitrate (7.94 mg Pb/L) for 60 days. Fish were distributed into four equal groups; T1 was kept as a control group, T2 was fed on 10 g R + C/kg feed, and T3 and T4 were fed on the control diet and 10 g R + C/kg feed, respectively, along with lead nitrate exposure. Findings of the present study indicated that, upon exposure to Pb (T3), growth, hemato-biochemical, and immune indices in Nile tilapia were notably reduced compared with that of the control group (T1). Meanwhile, stress (blood glucose, cortisol, total cholesterol, lactate dehydrogenase, alanine and aspartate aminotransferase, and alkaline phosphatase), hepatic oxidative stress (superoxide dismutase, catalase, and glutathione peroxidase) biomarkers, and DNA fragmentation percentage were significantly augmented in T3 vs T1. Additionally, exposing fish to lead nitrate caused immune suppression compared with the control group (T3 vs T1). On the other hand, the dietary supplementation of R + C mix to Nile tilapia (T2) enhanced its growth performance, antioxidant, and immune status. Feeding Pb-intoxicated Nile tilapia on R + C mix (T4) mitigated the oxidative damage and immune suppression induced by lead nitrate exposure compared with T3. Based on the present study outcomes, we opine that feeding Nile tilapia with rosemary plus cinnamon mixture (10 g/kg feed) has protective effects against lead nitrate-induced stress, physiological alterations, and oxidative damage.

Growth performance, hematological profile, and related genes expression in goldfish (Carassius auratus) fed on rosmarinic acid-enriched diets and subjected to ambient ammonia - Poulin Shohreh; Sedigheh Mohammadzadeh; Heba H. Mahboub; Ehsan Ahmadifar; Hassnaa Mahmoud Elsheshtawy; Naser Kalhor; Mohsen Shahriari Moghadam; Mohsen Abdel-Tawwab (Aquaculture, 2024)

Hypoxia alters the upper thermal limits and blood physiology in zebrafish, Danio rerio - Rayeda Jannat; Md Mahiuddin Zahangir; Azmaien Naziat; S.M. Majharul Islam; Aaser M. Abdelazim; Heba H. Mahboub; Md Shahjahan (Journal of Thermal Biology, 2024)

Silica nanoparticles alleviate the immunosuppression, oxidative stress, biochemical, behavioral, and histopathological alterations induced by Aeromonas veronii infection in African catfish (Clarias gariepinus) - Heba H. Mahboub; Wafaa M. Gad; Enas K. Aziz; Mona Abdelghany Nasr; Esraa M. Fahmy; Dina Mohamed Mansour; Nesma Rasheed; Hanaa S. Ali; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2024)
In the aquaculture industry, silica nanoparticles (SiNPs) have great significance, mainly for confronting diseases. Therefore, the present study aims to assess the antibacterial efficiency of SiNPs as a versatile trial against Aeromonas veronii infection in African catfish ( Clarias gariepinus ). Further, we investigated the influence of SiNPs in palliating the immune-antioxidant stress biochemical, ethological, and histopathological alterations induced by A. veronii . The experiment was conducted for 10 days, and about 120 fish were distributed into four groups at random, with 30 fish each. The first group is a control that was neither exposed to infection nor SiNPs. The second group (SiNPs) was vulnerable to SiNPs at a concentration of 20 mg/L in water. The third group was experimentally infected with A. veronii at a concentration of 1.5 × 10 7 CFU/mL. The fourth group ( A. veronii + SiNPs) was exposed to SiNPs and infected with A. veronii . Results outlined that A. veronii infection induced behavioral alterations and suppression of immune-antioxidant responses that appeared as a clear decline in protein profile indices, complement 3, lysozyme activity, glutathione peroxidase, and total antioxidant capacity. The kidney and liver function biomarkers (creatinine, urea, alkaline phosphatase, and alanine aminotransferase) and lipid peroxide (malondialdehyde) were substantially increased in the A. veronii group, with marked histopathological changes and immunohistochemical alterations in these tissues. Interestingly, the exposure to SiNPs resulted in a clear improvement in all measured biomarkers and a noticeable regeneration of the histopathological changes. Overall, it will establish that SiNPs are a new, successful tool for opposing immunological, antioxidant, physiological, and histopathological alterations induced by A. veronii infection.

Nano-liposome of thyme essential oil promotes growth performance, antioxidant and immune responses to aeromonad septicemia in Nile tilapia, Oreochromis niloticus, fingerlings - Morteza Yousefi; Seyyed Morteza Hoseini; Maryam Ghadamkheir; Heba H. Mahboub; Yury Anatolyevich Vatnikov; Evgeny Vladimirovich Kulikov; Elena Dmitriyevna Sotnikova (Frontiers in Marine Science, 2023)
Nano-encapsulation protects essential oils and increases their efficiency, compared to bulk forms. Hence in the present study, four diets (328 g/kg crude protein and 4402 kcal/kg gross energy) containing 0 (CTL), 25 mg/kg (25TV), 50 mg/kg (50TV), and 100 mg/kg (100TV) thyme, Thymus vulgaris , essential oil nano-liposomes (TV-NP) were offered to Nile tilapia fingerlings (initial weight of 4.27 ± 0.05 g) at water temperature of 26.46 ± 0.43°C, followed by intraperitoneal infection by Aeromonas hydrophila . Three hundred and sixty healthy fish were stocked in 12 tanks (60 L), 30 fish per tank, with daily water renewal rate of 40%. Each diet was offered to three tanks for 70 days. The fish were sampled at the end of feeding period and 12 h after the bacterial challenge. Compared to CTL, 50TV and 100TV treatments exhibited significant elevations in growth rate (14-17%; P<0.001), intestinal activities of amylase (9-19%; P=0.004), lipase (13-26%; P<0.001), protease (20-23%; P=0.001), and post-challenge survival (26-27%; P=0.001). Plasma lysozyme (14-15% P<0.001) and complement (5.1-5.4%; P=0.004) activities significantly increased in 25TV and 50TV, but decreased (lysozyme: 19%, complement 5.9%) in 100TV before the challenge; however, all TV-NP treatments showed similar lysozyme and complement activities after the challenge that were higher than CTL. 50TV and 100TV treatments also showed a decrease in lipid peroxidation (23-26%; P<0.001) and highest glutathione peroxidase activity (17-18%; P=0.001) and pre-challenge superoxide dismutase (21%; P=0.046) and catalase (15-17%; P=0.001) activities. Expression of tumor necrosis factor-alpha (11-fold, P<0.001), inerleukin-1 beta (5-fold, P<0.001), and transforming growth factor-beta (31-fold; P=0.001) in head kidney significantly increased in 100TV before the challenge. After the challenge, the transcripts of the cytokines significantly increased in all treatments and the highest expressions were observed in 50TV and 100TV treatments (62-148-fold). In conclusion, dietary 50-100 mg/kg TV-NP can be considered as a new feed additive in tilapia culture, as it improves growth rate, antioxidant capacity, and disease resistance in the fish.

Protective effect of Salvia hispanica (chia seeds) against obesity induced ovarian disorders in rat model - Eman Mahmoud FaragAllah; Samah Attia Algharib; Nehal I.A. Goda; Nanees F. El-Malkey; Heba H. Mahboub; Shaimaa H. El-Fayoumi; Nawal Al-Hoshani; Reham M. Wahid; Mohamed Aref (Tissue and Cell, 2023)

Hematological, immuno-antioxidant disruptions, and genes down-regulation induced by Aeromonas veronii challenge in Clarias gariepinus: The ameliorative role of silica nanoparticles - Afaf N. Abdel Rahman; Hassnaa Mahmoud Elsheshtawy; Engy Mohamed Mohamed Yassin; Ahmed Omran; Marwa Abo Hashem; Azhar Eltanahy; Tarek Khamis; Sameh H. Ismail; Morteza Yousefi; Heba H. Mahboub (Fish & Shellfish Immunology, 2023)

Exposure to oxyfluorfen-induced hematobiochemical alterations, oxidative stress, genotoxicity, and disruption of sex hormones in male African catfish and the potential to confront by Chlorella vulgaris - Abdallah Tageldein Mansour; Rehab M. Amen; Heba H. Mahboub; Sherif M. Shawky; Sahar H. Orabi; Amany Ramah; Heba S. Hamed (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Recent Insights into the Silver Nanomaterials: an Overview of Their Transformation in the Food Webs and Toxicity in the Aquatic Ecosystem - Syed Zaheer Ud Din; Khadim Shah; Nadia Bibi; Heba H. Mahboub; Mian Adnan Kakakhel (Water, Air, & Soil Pollution, 2023)

Influence of biosynthesized nanoparticles exposure on mortality, residual deposition, and intestinal bacterial dysbiosis in Cyprinus carpio - Mian Adnan Kakakhel; Nadia Bibi; Heba H. Mahboub; Fasi Wu; Wasim Sajjad; Syed Zaheer Ud Din; Ahmed A. Hefny; Wanfu Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Effect of Dietary Moringa oleifera Leaves Nanoparticles on Growth Performance, Physiological, Immunological Responses, and Liver Antioxidant Biomarkers in Nile tilapia (Oreochromis niloticus) against Zinc Oxide Nanoparticles Toxicity - Heba S. Hamed; Rehab M. Amen; Azza H Elelemi; Heba H. Mahboub; Hiam Elabd; Abdelfattah M. Abdelfattah; Hebatallah Abdel Moniem; Marwa A. El-Beltagy; Mohamed Alkafafy; Engy Mohamed Mohamed Yassin; Ayman K. Ismail (Fishes, 2022)
The current study addresses the influence of Moringa oleifera leaves nanoparticles (MO-NPs) on growth, biochemical, immunological, and hepatic antioxidant alterations induced by zinc oxide nanoparticles toxicity in Nile tilapia (O. niloticus). Fish (N = 180) were divided into four groups with replicates. The first one was set as a control group and the second group was fed an MO-NPs-enriched diet (2.5 g/kg diet). The third group was exposed to 8 mg/L ZnO-NPs, while the forth group was exposed to 8 mg/L ZnO-NPs and fed on MO-NPs (2.5 g/kg diet) for 2 months. Exposure of O. niloticus to 8 mg/L ZnO-NPs induced the following consequences: a sharp decrease in the growth parameters; a marked increment in the biochemical biomarkers (glucose, cortisol, and liver enzymes (ALT, AST, ALP); a significant increase in serum renal products, urea and creatinine, cholesterol, and LDH levels. Nonetheless, the dietary MO-NPs supplementation for 2 months significantly alleviated the ZnO-NPs toxicity and significantly enhanced the growth indices, plus normalizing the physio-biochemical levels in the exposed group to ZnO-NPs toxicity to reach the levels of the control group. The MO-NPs markedly improved hepatic antioxidant biomarkers, MDA, and TAC, while, decreasing SOD, CAT, and GSH levels to be near the control values. Moreover, supplemented fish in MO-NPs (2.5 g/kg diet) and exposed to ZnO-NPs provided a remarkable increase in the immune profile (respiratory burst (RB) activity, lysozyme, and total immunoglobulins (IgM)) compared to the ZnO-NPs-intoxicated group. Based on the findings of the study, the exposed O. niloticus to ZnO-NPs were immune-antioxidant-depressed, besides showing growth retardation, and physio-biochemical alterations. On the other hand, a supplemented diet with MO-NPs is a novel approach to ameliorate ZnO-NPs toxicity for sustaining aquaculture and correspondingly protecting human health.

Enhanced photodegradation of methylene blue from aqueous solution using Al-doped ZnS nanoparticles - Vijayan Selvaraj; Heba H. Mahboub; Umadevi Ganapathi; Senthil Kumar Chandran; Wedad Al-Onazi; Amal Mohammed Al-Mohaimeed; Tse-Wei Chen; Caterina Faggio; Balaji Paulraj (Environmental Science and Pollution Research, 2022)

The Dietary Effects of Nutmeg (Myristica fragrans) Extract on Growth, Hematological Parameters, Immunity, Antioxidant Status, and Disease Resistance of Common Carp (Cyprinus carpio) against Aeromonas hydrophila - Ghasem Rashidian; Khalid Shahin; Gehad E. Elshopakey; Heba H. Mahboub; Azin Fahim; Hiam Elabd; Marko D. Prokić; Caterina Faggio (Journal of Marine Science and Engineering, 2022)
Medicinal plants are increasingly used in aquaculture owing to their beneficial impacts on the health status of farmed fish. The current study was conducted to investigate the effect of nutmeg (Myristica fragrans) extract on growth, immunity, antioxidant parameters, and resistance of common carp (Cyprinus carpio) against Aeromonas hydrophila. In addition, in vitro antibacterial activity of the skin mucus of fish fed on nutmeg extract was evaluated against three major fish pathogenic bacteria through the standard disk diffusion method. Fish (17.27 ± 0.11 g) were divided into four groups and fed on experimental diets containing different levels of nutmeg extract, including zero (control), 0.5% (M1), 1% (M2), and 2% (M3) per kg diet. Results showed that nutmeg significantly enhanced growth parameters after a four-week feeding trial. Feed conversion ratio was remarkably reduced with the lowest value reported for the M3 group, whereas weight gain was notably increased in M2 and M3. No significant effect was found on the hematological profile, including mean corpuscular hemoglobin concentration, mean corpuscular hemoglobin, mean corpuscular volume, and hematocrit, while the highest levels of red blood cells and white blood cells were found in the M3 group. Stress biomarkers, including glucose and cortisol, were the lowest in the M3 group. Serum and skin mucus immunological and antioxidant parameters were significantly higher in M3, followed by M2, where the highest resistance was also observed. In addition, skin mucus samples effectively inhibited Streptococcus iniae, Yersinia ruckeri, and Aeromonas hydrophila. Overall, the present results suggest that dietary nutmeg (20 g/kg diet) could be used as a growth promotor and immunostimulant in common carp.

Bioremediation effect of pomegranate peel on subchronic mercury immunotoxicity on African catfish (Clarias gariepinus) - Zeinab M. El-Bouhy; Rasha M. Reda; Heba H. Mahboub; Fify N. Gomaa (Environmental Science and Pollution Research, 2021)